A study of the relationship between personality factors and attitudes towards perceived problem animals in white small-stock farmers of the Eastern Cape - Van Rensburg, Eureta Janse (Rhodes University, Faculty of Education, Department of Education, 1991)
This study explores a possible relationship between personality factors and attitudes towards perceived problem animals in a sample of 17 white, male, full-time small- stock farmers in the Eastern Cape district of Cradock. Personality factors were analysed by means of Cattell's l6 Personality Factor Questionnaire, standardised for South Africa. Attitudes were determined by qualitative analysis of data from semi-structured interviews. Specific personality factors associated with positive and negative attitudes towards 'problem animals', including Lynx Felis caracal, eagles and vultures, were identified. Demographic and situational influences and certain world views associated with environmental attitudes are also discussed. Re-orientation of perspectives are recommended for farmers, conservationists and environmental educators.
Keywords: Conservation of natural resources -- South Africa; Farmers -- Psychology